ASPECTS OF MICROTOPOGRAPHY OF MINERAL SURFACES IN MODELING OF MINERAL FORMATION PROCESSES ON THE EXAMPLE OF GARNETS - KVASNYTSIA, Iryna (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
Background. Microtopographic studies of the crystal faces provide a large amount of information about the origin of the crystal, the mechanisms of crystallization, the details of the growth process, the environment, the further existence and gradual destruction of the mineral, allow predicting the possible behavior of crystals in the enrichment process, etc. The faces of real crystals are non-smooth, rough, have an uneven surface and are often covered with a large number of flat and curved microform-microfaces. The face microrelief reflects the interaction of the crystal structure of the mineral and the mineral formation environment; the symmetry of simple microrelief forms of a certain origin is the result of the interaction of the symmetry of the crystal structure and the symmetry of the mineral formation environment. The elements of the crystal surface microtopography (microrelief) traditionally include growth and dissolution figures, as well as more complex sculptures consisting of more microfaces.  Methods. Goniometry and scanning electron microscopy (REMMA-202M electron microscope, JSM-6700 F electron microscope) were used to study the morphology and microtopography of the garnet crystals surface (spessartine (the Nani hill deposit, Loliondo, Tanzania), andradite (Smerekiv Kamin', Vygorlat-Gutyn hills, Transcarpathian, Ukraine). Results. The studied garnet crystals are characterized by a variety of surface relief forms inherent in both the growth process (growth steps, protrusion strokes, meanders) and dissolution (dissolution pits, strips with dissolution pits, tiled dissolution pattern, trichitic channels). Сonclusions. The studied crystals of spessartine obviously changed their shape in the process of growth, since the faces have a rough sculpture (striations, numerous rough growth hillocks, etc.). This statement is also supported by the presence of coarse striation on individual faces of spessartine. The presence of a meander relief indicates the formation of crystals in a solid enviroment by substitution. The surfaces of andradite crystals, which are part of the vein-type skarn mineralization, mostly show numerous signs of dissolution, including a dentate-stepped relief, and the replacement of garnet by fissures with secondary minerals (calcite, less often chlorite), which indicates a long and multi-stage process of metasomatic changes.
Keywords: microtopography; microrelief; growth and dissolution sculptures; garnet; andradite; spessartine